Provisional Growth Estimate of Lagerstroemia hypoleuca (Pyinma) - Singh, S. P.; Sharma, R. S. (Indian Forester, 1983)
Information on growth of Lagerstroemia hypoleuca (Pyinma) is scanty and no attempt was made to estimate period of harvest for this species. Though the growth data is limited, yet attempt is made to study its growth pattern and project the same in the form of yield table.